Sand Flies Fauna Involved in the Transmission of Cutaneous Leishmaniasis in Afro-Colombian and Amerindian Communities of Choco, Pacific Coast of Colombia (2004)
ABSTRACT: - A prospective study was conducted on the diversity of phlebotomine in the pacific coast of Colombia and its relationship with the eco-epidemiology of leishmaniasis. A total of 5,365 phlebotomines were collected on light traps, in human baits also standing still on walls, trees and mammalian caves. In total, 42 phlebotomine species were identified belonging to the genera Lutzomyia, Brumptomyia and Warileya. Among these, the highly anthropophilic vector species Lutzomyia gomezi (Nitzulescu), Lu. hartmanni (Fairchild & Hertig) and Lu. trapidoi (Fairchild & Hertig). Leishmania panamensis was the main parasite species affecting the population, with a prevalence of 57% in Indians and 26% in black people. In the Indian community no difference was found in the skin test (Montenegro) between sexes, being positive in 57% of indian males and 58.5% in indian females. In contrast, 39% of black males and 10% black females were found to be positive in the skin test. These results confirm that the transmission of L. panamensis in the studied area is restricted to the rural areas and linked to people activities and the location of their homes.